DETERMINING OF THE RELEVANCE THREATS OF INFORMATION SECURITY IN INDUSTRIAL CONTROL SYSTEMS - Гончар, Сергій Феодосійович (Ukrainian Information Security Research Journal, 2015)
In order to solve problems related to the information security in the industrial control systems shows a generalized model of information security. The studies and analysisof the interaction between the system of information security and destabilizing factors such as threats, favorable conditions for the realization of these threats, vulnerabilities are realized. It was shown that the relevance ofthe information security threats is proportional to theprobability of the threat and the ratio of its danger is show. Expressions for the determination of the likelihoodof threats to information security and the coefficient of itsdanger are given. A method for determining the actual information security threats in the automated process control systems, and formulated the initial data neededfor this are given.